IRAMY Inverter Control for Solar Electric Vehicle - Rachid Taleb; Hemza Saidi (Institute of Advanced Engineering and Science, 2016)
Solar Electric Vehicles (SEV) are considered the future vehicles to solve the issues of air pollution, global warming, and the rapid decreases of the petroleum resources facing the current transportation technology. However, SEV are still facing important technical obstacles to overcome. They include batteries energy storage capacity, charging times, efficiency of the solar panels and electrical propulsion systems. Solving any of those problems and electric vehicles will compete-complement the internal combustion engines vehicles. In the present work, we propose an electrical propulsion system based on three phase induction motor in order to obtain the desired speed and torque with less power loss. Because of the need to lightweight nature, small volume, low cost, less maintenance and high efficiency system, a three phase squirrel cage induction motor (IM) is selected in the electrical propulsion system. The IM is fed from three phase inverter operated by a constant V/F control method and Space Vector Pulse Width Modulation (SVPWM) algorithm. The proposed control strategy has been implemented on the texas instruments TM320F2812 Digital Signal Processor (DSP) to generate SVPWM signal needed to trigger the gates of IGBT based inverter. The inverter used in this work is a three phase inverter IRAMY20UP60B type. The experimental results show the ability of the proposed control strategy to generate a three-phase sine wave signal with desired frequency. The proposed control strategy is experimented on a locally manufactured EV prototype. The results show that the EV prototype can be propelled to speed up to 60km/h under different road conditions.